Suboxone: History, controversy, and open questions - Sivils, Andy; Lyell, Paige; Wang, John Q.; Chu, Xiang-Ping (Frontiers in Psychiatry, 2022)
There are more than 200 opioid overdose deaths each day in the US. In combating this epidemic we look to available treatment tools. Here, we find only three medications approved by the FDA for the treatment of opioid use disorder. Of the three, buprenorphine is of particular importance due to its reduced overdose potential as a partial opioid agonist. Evidence supports its clinical equivalence to its full agonist cousin methadone, and suggests that it is better slated for long-term treatment of opioid use disorder compared to the non-selective opioid antagonist naltrexone. Buprenorphine is most popularized within Suboxone, a medication which also contains the non-selective opioid antagonist naloxone. The naloxone has no additional effect when the drug is taken as instructed, as it is intended to prevent diversion in those that would attempt to inject the medication. While Suboxone is regarded by some as the future of medical treatment, others have expressed concerns. This review aims to explore the history, controversy, and open questions that surround buprenorphine and its most prescribed variation, Suboxone. These include its pharmacological, legislative, and social history, alternative indications, efficacy as a treatment of opioid use disorder, and more. Armed with this information, the reader will have a more in-depth and holistic understanding of the medication’s place in their community.